Tailored Microstructure in Laser-Based Powder Bed Fusion of Polymers - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (Annual Technical Conference - ANTEC, Conference Proceedings, 2024)
Currently, the Laser-based powder bed fusion of polymers (PBF-LB/P) mainly uses polyamides, which prevents the components from exhibiting the mechanical characteristics of traditional manufacturing techniques. As a result, highly ductile and chemical-resistant materials are needed to cover more potential application areas. The preferred material is polypropylene (PP) with its various structures and settings. A common practice in conventional manufacturing processes is adjusting the morphology of the component, but studies examining this type of influence in PBF-LB/P are scarce. This work first introduces possible nucleation agents and subsequently, alongside the analytical investigation, manufactures components to assess the impact of the structure. It was concluded that processing the material is possible despite higher crystallization kinetics. For the first time, it was possible to process β -nucleated PP, demonstrated by the production of mechanical test specimens.
CRIS-Team Scopus Importer:2025-02-04